Poly(o-aminophenol) a polymer employed as material of biosensors: Its deactivation : A review article - Tucceri, Ismael Ricardo (2017)
Electrochemical and chemical treatments, such as, storage time without use (STWU), prolonged potential cycling (PPC), high positive potential limits (HPPL) and soaking in a ferric ion solution (SFeIS), affect the conduction properties of poly (o-aminophenol) (POAP). The effect of these treatments on the conducting properties of POAP was studied employing cyclic voltammetry (CV), rotating disc electrode voltammetry (RDEV), electrochemical impedance spectroscopy (EIS) and surface resistance (SR). A review of these studies is presented in this work.